The Potential Harm of Prostate Cancer Health Supplements. (November 2015) - Patel, Minesh; Musa, Faisal; Mousi, Fahd; Landau, Daniel
Introduction . Products that advertise "prostate health" are readily available at most major supplement and vitamin shops. The SELECT trial, SELenium and vitamin E Cancer prevention Trial, showed that men who were supplemented with vitamin E and selenium faced a higher risk of developing prostate cancer. We opted to look at nationally available products from major retailers that advertised prostate health to determine if they could potentially cause harm by inclusion of selenium and/or vitamin E. Methods . We collected data from national retailers including Vitamin Shoppe, General Nutrition Corporation (GNC), that sell vitamins and supplements. Any product that advertised terms such as "prostate health" or "prostate cancer prevention" or similar were analyzed. In total, 97 products were assessed. The ingredients were analyzed to see if the product contained selenium or vitamin E. The remaining ingredients were also recorded. Results . Of all the products, 17% contained both selenium and vitamin E, 36% had selenium without vitamin E, and 16% had vitamin E without selenium. Overall, more than 50% contained selenium. Of the products containing selenium, 35% had 200 µg daily; the amount used in the SELECT trial. Of the products containing vitamin E, none had the 400 IU used in the SELECT trial. The most common ingredient used in the nationally available supplements advertised for prostate health was saw palmetto, with 85% containing this ingredient. Conclusion . Nearly one fifth of all products advertised for prostate health contained both selenium and vitamin E, although vitamin E was at levels lower than used in the SELECT trial. Selenium was, however, much more common and often at the doses per the SELECT trial. These data do not take into account other supplements and vitamins that people may be taking that also contain these ingredients. According to results from the SELECT trial, products that contain selenium and vitamin E should not be used for prostate health. Patients should exercise caution in selecting nonprescription therapies for prostate health and should receive education from their physicians or pharmacists if seeking these products.